Privatization of Land Plot Under Integral Real Estate Complex - A. A. Maruchek; M. V. Sharikova (Сибирское юридическое обозрение, 2014)
The article deals with the questions concerning the privatization of a land plot under integral real estate complex. The authors come to conclusion that a number of legislation norms relating to privatization of a land plot do not take into account the construction of an integral real estate complex that could cause some problems in the realization of the right to privatization of the land plot.